Development without aid : the problems of development aid and a prospect for ending it - Phillips, David A. (David Anthony) (Anthem studies in development and globalization, 2013)
?Development Without Aid" opens up perspectives about foreign aid to the world's poorest countries. Growing up in Malawi the author developed a sense of the limitations of foreign assistance and from this evolves a critique of foreign aid as an alien resource unable to provide the dynamism that could propel the poorest countries out of poverty. The book aims to help move the discussion beyond foreign aid. It examines the rapid growth of the world's diasporas as a quasi-Indigenous resource of increasing strength in terms of both financial and human capital, and considers how far such a reso